Strengthening Character Education in Schools through the Strengthening Pancasila Profile Project (P5) - Nofrita, Misra; Nazurty, Nazurty; Fitrah, Yundi; Karim, Maizar; Hendri, M (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2023)
Character education is currently very much needed in character building, especially at the school level, especially through the profile of Pancasila students. The goal to be achieved in this research is to describe character education through the profile of Pancasila students. This research is a literature review type. The independent variable in this study is Character Education and the dependent variable is the Pancasila student profile. The population in this study used all research journals on the topic of character education and Pancasila student profiles. The results state that strengthening character education is carried out through the Pancasila project profile. Where the Pancasila project profile can provide character strengthening, especially at the school level with the target of students.